2013
DOI: 10.1111/1755-5922.12001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levosimendan on Estimated Glomerular Filtration Rate in Hospitalized Patients with Decompensated Heart Failure and Renal Dysfunction

Abstract: SUMMARYBackground: Only limited data of the long-term effect of levosimendan on renal dysfunction in patients with decompensated heart failure (DHF) have been published previously. To date, there has been no similar study carried out in a Chinese population. Design and Methods: A prospective, randomized, placebo-controlled, and double-blind study was performed to investigate the effect of levosimendan on estimated glomerular filtration rate (eGFR) in DHF patients with renal dysfunction during a 30-day period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 27 publications
1
22
0
2
Order By: Relevance
“…Several mechanisms probably account for the elevated BNP levels in sepsis, including neuro-hormonal activation, volume resuscitation, and sepsis-induced biventricular dilation [ 32 ], as well as stimulation of lipopolysaccharide or pro-inflammatory cytokines, acute lung injury, and acute respiratory distress syndrome induced sepsis [ 33 ]. Levosimendan was found to have significantly decreased BNP levels at Day 1 and Day 3 in patients with decompensated heart failure (DHF) and renal dysfunction [ 34 ]. Feola et al demonstrated that BNP concentrations decreased more significantly in a levosimendan group than a furosemide group [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms probably account for the elevated BNP levels in sepsis, including neuro-hormonal activation, volume resuscitation, and sepsis-induced biventricular dilation [ 32 ], as well as stimulation of lipopolysaccharide or pro-inflammatory cytokines, acute lung injury, and acute respiratory distress syndrome induced sepsis [ 33 ]. Levosimendan was found to have significantly decreased BNP levels at Day 1 and Day 3 in patients with decompensated heart failure (DHF) and renal dysfunction [ 34 ]. Feola et al demonstrated that BNP concentrations decreased more significantly in a levosimendan group than a furosemide group [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This understanding is exemplified by rolofylline-and the PRO-TECT hypothesis that improving renal blood flow and function could improve outcome in AHF-despite the neutral results of the PROTECT study [16]. Levosimendan has demonstrated renoprotective effects, albeit with inconclusive survival effects, further supporting the hypothesis that vasodilators can benefit renal function in AHF [84,91].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported positive effects of Levosimendan treatment on renal function [81][82][83][84]. The explanation likely lies with levosimendan's vasodilator activity, with stronger venous compared to arterial vasodilation, along with its positive inotropic effects [85].…”
Section: Levosimendanmentioning
confidence: 99%
“…Hou и соавт. отмечали, что 24-часовая инфузия левосимендана по сравнению с плацебо увеличивала СКФ в течение 14 дней после инфузии у пациентов с ОДСН [27]. Также Zorlu и соавт.…”
Section: результатыunclassified